Systematic review of the impact of unemployment on levels of happiness - Barros, Carlos André Vilas Boas Rosa (2016)
The wealth on na economy is traditionally measured by its level of productivity. However, do countries with the highest level of productivity report equal levels of happiness and general well-being? As a matter of fact, there is no direct relationship between both variables and there can actually be, from a productive point of view, less wealthy countries reporting higher levels oh hapiness. hence, there have been recente studies and theriores- such as the Economics of Happiness- that are attempting to demonstrate the term hapiness has made its way into economics literature as the result of the dissatisfaction of economists who believe hapiness should become a matter of study in economics. Onde of the variables aconomists most research about- unemployment- has a direst relationship with happiness, which is why it is particular importante for economics to study it. As many authors have been suggesting, arguing and proving, the autonomy- both methodological and philsophial-, reliability and added value of happiness would contribute fo a more complete economic analysis. Althougth there have beeen many failed attempts to incorporate happiness as a study variable in economics, this new current is expected to succeed, not only due to the rising importance of happiness in people`s daily lives, but also, and mostly, due to the increasing number of authors that are investigating and defending it beingn studied by economics. The fact that this time the "happiness" variable is seen as multidisciplinar and not only assigned to na economic point economics will not come to fail this time around.